Latihan Range of Motion Terhadap Rentang Gerak Sendi Ekstremitas Atas Pasien Stroke di RSUD M.Natsir - Tintin - Sumarni; Yulastri Yulastri (Poltekkes Kemenkes Padang, 2021)
Stroke patients who experience hemiparese who do not receive proper treatment can cause complications of functional disorders, impaired mobilization, disruption of daily activities and incurable disabilities. The purpose of this study was to determine the effect of passive Range Of Motion (ROM) exercise on increasing the range of motion of stroke patients in the Neurology Room at RSUD M.Natsir.This research design is quasi experimental with the design used is one group pretest - postest design.In this study, passive Range Of Motion (ROM) was performed on the upper extremities of stroke patients for five days, twice a day.The number of respondents in 30 stroke patients who experienced hemiparese,The data was collected by direct measurement using a measuring instrument for the degree of motion of the joints, namely the goniometer, and data analysis was carried out using the t dependent test (normally distributed data).The results showed a significant difference in the range of motion of the upper limb joints before and after passive ROM exercises. The conclusion that ROM exercises affect the range of motion of the upper limb joints in stroke patients.Passive ROM can be an alternative to increase the range of motion of the joints in the upper and lower extremities in stroke patients.